Contribution of advanced agroforestry research in sustaining soil quality for increased food production and food security - PRASAD, RAJENDRA; DHYANI, S. K.; NEWAJ, RAM; KUMAR, SUDHIR; TRIPATHI, V. D. (Journal of Soil and Water Conservation, 2020)
Agroforestry is a land use system that combines agriculture and forestry. From the beginning, the major tenets of agroforestry have been its soil conservation value and sustainability of agricultural production system. The scientific community intervened to harness full benefits of agroforestry land use system and address global issues of land degradation, agricultural sustainability and more recently the climate change and food security. The horizontal (expansion of area) and vertical (innovative research) growth of agroforestry has made significant stride towards wellbeing of the people. The surging interest in agroforestry to search solution for global problem of climate change and food security is based on the scientific revelations that the tree components of agroforestry not only supplement and compliment growth of agro-components by improving soil health but also contribute toward mitigation of climate changes and food security. This review is an attempt to organise research advances of agroforestry in logical order to understand contribution of agroforestry towards complex problems of maintaining soil fertility, meeting goals of climate change and food security. The paper also lists some of the research gaps for future.